2005
DOI: 10.1080/00365520410009537
|View full text |Cite
|
Sign up to set email alerts
|

Caution in the use of boldo in herbal laxatives: A case of hepatotoxicity

Abstract: A case is reported in which a several-fold increase in transaminases and gamma-GT was detected in an elderly male patient with fatty liver. The patient was regularly taking a mixture of herbal products, used as a laxative, for a number of years, with no alteration of blood chemistry until 6 months before the present observation. However, the composition of the mixture had been modified by the manufacturer in the past 5 months, with addition of boldo leaf extracts. Transaminases promptly returned to normal afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 7 publications
1
3
0
2
Order By: Relevance
“…However, a reorganization of the actin filaments and increased transcriptional level of relevant markers of cellular activation occured (Fig. 2), suggesting profibrotic signaling activation, which corroborates studies that point to P. barbatus toxicity when used in high concentrations [65, 66]. Moreover, the extract also acted directly on cellular lipid metabolism, reinforcing popular culture, which uses the extracts as a liver fat metabolizer [16, 67, 68].…”
Section: Discussionsupporting
confidence: 80%
“…However, a reorganization of the actin filaments and increased transcriptional level of relevant markers of cellular activation occured (Fig. 2), suggesting profibrotic signaling activation, which corroborates studies that point to P. barbatus toxicity when used in high concentrations [65, 66]. Moreover, the extract also acted directly on cellular lipid metabolism, reinforcing popular culture, which uses the extracts as a liver fat metabolizer [16, 67, 68].…”
Section: Discussionsupporting
confidence: 80%
“…In this study, the use of leaves-derived aqueous extract A case is reported in which a several-fold increase in transaminases and g-GT was detected in an elderly male patient with fatty liver in use a laxative with addition of boldo leaf extracts concluding this extracts might be hepatotoxic, at least in elderly patients with fatty liver 27 . On the other hand, lower doses of the same extract, ranging from 20 to 40 mg/Kg, have demonstrated to ameliorate toxicity generated by cisplatin in liver tissue in vivo 11 .…”
Section: Discussionmentioning
confidence: 79%
“…Peumus boldus is a tree which grows in the South American Andes and is traditionally used for symptomatic treatment of dyspepsia, mild gastrointestinal spasmodic disorders and painful joints [2] . However, the number of reported cases of possible hepatotoxicity is increasing [1,3] . It is still not widely known that herbal medicines commonly cause adverse events, and their pathogenic mechanisms have not been sufficiently investigated.…”
Section: Discussionmentioning
confidence: 99%